Polling on Public Policy: A Case Study in Engaging Youth Voters in the Public Opinion Process for Effective Civic Discourse. (May 2014) - Kimball, Spencer; Payne, J.Gregory
This report details the steps involved in setting up a polling club as part of related classes in political communication, public policy, and civic engagement among college students. It also examines an extracurricular activity that provides students with the opportunity to assess public opinion on policy matters at the local, state, and national levels. Insights as well as challenges from professors and students involved in such pertinent themes as web analytics, aggregate polling, and the internal and external constraints and biases inherent in such a project will be explored, as well as the need to focus on an integrated strategic communication perspective that bridges the frequent silos of marketing, advertising, public relations, journalism, and political communication.